2013
DOI: 10.1016/j.plaphy.2013.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Vitis vinifera secondary metabolism as affected by sulfate depletion: Diagnosis through phenylpropanoid pathway genes and metabolites

Abstract: Grapevine (Vitis vinifera L.) is rich in phenylpropanoid compounds, namely flavonoids and stilbenes which, present in most tissues, are described as antioxidants and known to accumulate in response to biotic and abiotic stress. Grapevine is then a choice model for studying the interplay between the phenylpropanoid pathway and nutrient deficiency. Here we report the response to sulfur deficiency (-S) of flavonoids and stilbenes biosynthetic pathways in chlorophyll tissues (plantlets) and cell culture. Anthocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…While Larronde et al (1998) reported on only a slight modulating effect of sucrose application on stilbene production, Ferri et al (2011) demonstrated that increasing sucrose concentrations promote stilbene production in the cell suspensions. Tavares et al (2013) reported that stilbene biosynthesis in photosynthetic and nonphotosynthetic tissues of V. vinifera is affected by sulfur deficiency. In response to the sulfate depletion conditions, t-resveratrol and e-viniferin accumulated in the grapevine plantlets, while t-resveratrol glucoside accumulated in cell suspension cultures of V. vinifera.…”
Section: Transcriptional Regulation Of Stilbene Biosynthesis In Plantsmentioning
confidence: 99%
“…While Larronde et al (1998) reported on only a slight modulating effect of sucrose application on stilbene production, Ferri et al (2011) demonstrated that increasing sucrose concentrations promote stilbene production in the cell suspensions. Tavares et al (2013) reported that stilbene biosynthesis in photosynthetic and nonphotosynthetic tissues of V. vinifera is affected by sulfur deficiency. In response to the sulfate depletion conditions, t-resveratrol and e-viniferin accumulated in the grapevine plantlets, while t-resveratrol glucoside accumulated in cell suspension cultures of V. vinifera.…”
Section: Transcriptional Regulation Of Stilbene Biosynthesis In Plantsmentioning
confidence: 99%
“…In normal conditions, various plants and plant cell cultures contain low t‐ resveratrol levels (up to 0.1 mg/g of dry weight [mg/g DW]), and the use of different elicitors did not result in a considerable and constant increase in t‐ resveratrol production . The level of t‐ resveratrol in cell cultures of V. vinifera , Vitis amurensis , Gossypium hirsutum , and Arachis hypogaea treated with various compounds and conditions, for example, methyl jasmonate (MeJa), salicylic acid, ultraviolet C, sucrose, or sodium nitroprusside, did not exceed 0.5% DW or 5 mg/g DW . The most significant success in increasing resveratrol content in plant cell cultures has been reached using cyclodextrins (CDs).…”
Section: Introductionmentioning
confidence: 99%
“…The pathway passing though the STS-catalyzing reaction is called the stilbenoid biosynthetic pathway, and the pathway through the CHS-catalyzing reaction is the flavonoid biosynthetic pathway. The substances synthesized through these metabolic pathways are secondary metabolites used to increase plant adaptability to environmental conditions (Tavares et al, 2013). Biotic and abiotic stresses have been demonstrated to be responsible for polyphenol accumulation, such as anthocyanin accumulation (Winkel-Shirley, 2002).…”
Section: Plant Materialsmentioning
confidence: 99%
“…In red wine grapes, abiotic stresses from several treatments enhance the gene expressions of STS and CHS and the biosynthesis of polyphenols including trans-resveratrol and flavonoids (Bonghi et al, 2012). In the context of biosynthesis progression, polyphenol oxidase, laccase, and peroxidase play important roles in metabolic pathways such as lignin biosynthesis and phenol compound polymerization (Pezet et al, 2003;Tavares et al, 2013;Zamboni et al, 2010). Recently, molecular bases for the regulation of these biosynthetic pathways have been researched intensively in grapevine (Czemmel et al, 2012;Tillett et al, 2011;Vannozzi et al, 2012).…”
Section: Figmentioning
confidence: 99%